Public Health, Health Management, Clinical Audit and Forensic Sciences in Dentistry as Specialty Postgraduate Training Programs - Manrique Chávez, Jorge Enrique (2021)
Objective: Tsystematize the experience of curricular design and competencies management for the creation of postgraduate and specialization programs in Public Health, Health Management, Clinical Audit and Forensic Sciences in Stomatology. Material and Methods: A historical review and documentary analysis of the period 2011-2021 of the continuing education courses, diplomas and second professional specialties developed by the Academic Department of Social Dentistry in the fields of Public Health, Health Management, Clinical Audit and Forensic Sciences in the Postgraduate and Specialization Unit of the Faculty of Stomatology of the Universidad Peruana Cayetano Heredia. Results: A “Model of Fields of Knowledge for Curriculum Design and Competency Management for Postgraduate and Specialization Programs in Public Health, Health Management, Clinical Audit and Forensic Sciences in Dentistry” was designed that brings together a set of competencies, specific axes (essential) and general axes (complementary). Conclusions: Through a Competency-Based Learning approach and following the guidelines of Education in Dentistry, fields of knowledge were structured that allowed the creation of second professional specialties in Dental Public Health, Dental Practice Management, Dental Audit and Forensic Dentistry at the Faculty of Stomatology of the Universidad Peruana Cayetano Heredia.